Banjar Archaic Vocabulary: An Anthropological Linguistic Studies - Kamariah; Kisyani; Mintowati (TALENTA Publisher, 2022)
Banjar archaic is an ancient ethnic Banjar language that some speakers still speak in remote areas or older speakers. Banjar archaic language is unique in terms of disclosure, so it is exciting to research. Banjar's archaic vocabulary must be well documented so that the vocabulary does not disappear over time. This study aims to identify the vocabulary of the Banjar language archaic and describe the class category of Banjar archaic. The method used in this research is a qualitative descriptive method with the emic approach. The subject of this study was the Banjar ethnic community with an age range of 40-65 years. The research was conducted in Peat Subdistrict, Banjar Regency. The results showed that the vocabulary of Banjar language archaic is still used by Banjar ethnicity, as evidenced by the discovery of eighty-eight vocabulary with four types of word classes, namely nouns, verbs, adjectives, and numerals. Of the four types of word classes, which are still widely used are the class of nouns in the form of basic nouns and compound nouns. While the least is numeral found only one vocabulary. The surviving vocabulary of Banjar archaic is caused by several factors of community culture, namely farming and community patterns that still uphold Banjar customs.